Un-silencing “Conversion therapies” of LGBTIQ+ people in Africa: Exploring the doctrine of the Trinity towards inclusive families : Queering Ruth and Boaz’s encounter at the threshing floor - Davids, Hanzline (Stellenbosch Theological Journal, 2022)
Lesbian, gay, bisexual, transgender, intersex, queer, and plus all other (LGBTIQ+) people often are being “corrected” by families through religious and cultural beliefs because of their sexual orientation, gender identity, expression, and sex characteristics (SOGIESC) that destabilises stable constructs of heteronormativity. For these belief systems, LGBTIQ+ people threaten the concept of family and associated values that inform the so-called social fabric and cohesion of sexuality and gender norms. In recent years, LGBTIQ+ people, human rights defenders, and academics have shed light on the practices of “conversion therapies” on the African continent in various forms as practised by religious and cultural communities. “Conversion therapy” is also called “reparative therapy” or “gay cure” interchangeably to describe different practices that are out to change, suppress or dissuade LGBTIQ+ people’s sexual orientations, gender identities and expressions. This article will use short narrative audio video interviews conducted by openDemocracy to give voice to survivors of “conversion therapy” on the African continent. In these videos, survivors speak about the intersectional reality of family relations, mental health and religion’s impact on their well-being. Over the last few years, there has been a reappreciation of the doctrine of the Trinity. Bisexual Latin-American theologian Marcella Althaus-Reid views the Trinity as a critique of heteronormative binaries. Therefore, this article explores whether Althaus Reid’s Trinitarian theology offers a counter theological narrative against “conversion practices” as advocated by families based on religion.